2012
DOI: 10.1371/journal.pone.0034798
|View full text |Cite
|
Sign up to set email alerts
|

The Human Operculo-Insular Cortex Is Pain-Preferentially but Not Pain-Exclusively Activated by Trigeminal and Olfactory Stimuli

Abstract: Increasing evidence about the central nervous representation of pain in the brain suggests that the operculo-insular cortex is a crucial part of the pain matrix. The pain-specificity of a brain region may be tested by administering nociceptive stimuli while controlling for unspecific activations by administering non-nociceptive stimuli. We applied this paradigm to nasal chemosensation, delivering trigeminal or olfactory stimuli, to verify the pain-specificity of the operculo-insular cortex. In detail, brain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…Similarly to a previous experiment employing similar stimuli (Lötsch et al, 2012), the nociceptive stimuli were always perceived as painful (median [interquartile range]: 48.63 [33.19, 67.44] mm VAS pain) but not smelly (0 [0.0, 6.31] mm VAS smell), whereas the H 2 S and vanillin were rated as smelly (31.44 [19.43, 47.5] and 22.06 [9.0, 31.9] mm VAS smell, respectively) but not painful (0 [0.0, 0.0] mm VAS pain). THC altered neither intensity perception (interaction 'drug' by 'measurement': F(1,14) = 3.16, p = 0.097) nor pleasantness rating (interaction 'drug' by 'measurement': F(1,14) = 0.391, p = 0.542) of the painful CO 2 stimuli.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly to a previous experiment employing similar stimuli (Lötsch et al, 2012), the nociceptive stimuli were always perceived as painful (median [interquartile range]: 48.63 [33.19, 67.44] mm VAS pain) but not smelly (0 [0.0, 6.31] mm VAS smell), whereas the H 2 S and vanillin were rated as smelly (31.44 [19.43, 47.5] and 22.06 [9.0, 31.9] mm VAS smell, respectively) but not painful (0 [0.0, 0.0] mm VAS pain). THC altered neither intensity perception (interaction 'drug' by 'measurement': F(1,14) = 3.16, p = 0.097) nor pleasantness rating (interaction 'drug' by 'measurement': F(1,14) = 0.391, p = 0.542) of the painful CO 2 stimuli.…”
Section: Resultsmentioning
confidence: 88%
“…Based on previous neuroimaging studies on the framing effect described in the introduction (De Martino et al, 2006), we hypothesized that emotional areas such as anterior insula and amygdala, were involved in processing the frame; moreover, further imaging studies reported activations in the operculo/insular cortex associated with pain processing (e.g., Lötsch et al, 2012) and in interoceptive awareness and the representation of visceral responses associated with emotional situations (Lamm et al, 2007). Thus, a hypothesis-driven region of interest (ROI) analysis (Friston, 1997) was performed in which we tested significant increases of neural activity in the operculo/insular cortex [Anatomy Toolbox (Eickhoff et al, 2005)], for the main effect of frame.…”
Section: Resultsmentioning
confidence: 99%
“…1,10,49 Additional research has revealed that functional areas associated with the pain matrix may also be activated in response to nonpainful stimuli. 2,36,46 This may be directly re-…”
Section: Discussionmentioning
confidence: 99%
“…36 It has also been proposed that areas within the pain matrix may include an evaluative component to discern whether the sensory input is potentially threatening. 33,45 We hypothesized that a change in cerebral blood flow, in the form of decreased activation of the areas associated with pain perception, would occur following thrust manipulation to the thoracic spine, and a significant relationship would exist between reduction in pain perception and change in cerebral activation.…”
Section: Discussionmentioning
confidence: 99%